Go West, czyli bracia Marx dosiadają żelaznego konia - Pomostowski, Piotr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
The article is about the tenth image by famous Marx Brothers. Author of the text carried out a thorough analysis of the film Go West for the current in the game with western conventions. The text consists of five parts – introduction and four separate mini-chapters. In the first context the statement made b y the film Go West (by Edward Buzzel) the masterpiece of silent cinema – Iron Horse directed by John Ford, seeing the first image of a series of references to the other one. The second part is devoted to the image of Indians in the film Go West in the context of the existing schemes in the cinema of the thirties and forties. In the next section the author discusses the functions used in film music, and in the last – the final chase sequence, seeing in it references to the tradition of film slapstick. In conclusion, the author states that the game with conventions manifests itself not only in the film for a specific genre, but also the cinema in general, which in 1940 was an innovative solution.